(untitled) (Research, Society and Development, 2021)
The general aim of this research was to analysis the articulation between family and school in a perspective of a Field Education and its implications for the education of students. For this, the director, teachers and school community participated, represented by mothers and fathers of students, all from the municipality of Serra do Ramalho-BA, Brazil. The methodology was guided by the principles of the qualitative approach with the case study, with information collect through two questionnaires and analysis of the Pedagogical Political Project (PPP). The results indicate positive relationships, pointed out, especially out respect and harmony. Mothers and fathers seek to participate in their children’s school life, information endorsed by the teachers, who point to the need for greater investment in this process, as long as the roles of each one are made explicit. The evidence also indicates gains, on the part of students, in families whose participation is more incisive in school monitoring and school decision-making. Finally, it proposes na effective dialogical relationship, through a series of actions that meet the singularities of the peasant community, as well as its history of struggle and trajectory of conquests.